Transactions on Aspect-Oriented Software Development VI Special Issue on Aspects and Model-Driven Engineering - Katz, Shmuel; Ossher, Harold (Transactions on Aspect-Oriented Software Development,, 2009)
The LNCS journal Transactions on Aspect-Oriented Software Development is devoted to all facets of aspect-oriented software development (AOSD) techniques in the context of all phases of the software life cycle, from requirements and design to implementation, maintenance and evolution. The focus of the journal is on approaches for systematic identification, modularization, representation and composition of crosscutting concerns, and evaluation of such approaches and their impact on improving quality attributes of software systems. This volume, the sixth in the Transactions on Aspect-Oriented Software Development series, focuses on the theme of aspects and model-driven engineering. The seven papers included in this issue give an in-depth coverage of the following topics: methods and techniques supporting separation, composition, and evolution of aspects identified in different development phases; simulation of runtime weaving of aspects using aspect-oriented models; techniques for verifying and validating aspect-oriented models; AOM case studies that provide significant insights into how aspect-oriented modeling techniques can be applied across the development life-cycle; tool support for use of integrated AOSD and MDE techniques; and language support for aspect-oriented modeling.